PENGARUH KOMPENSASI, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT KURNIA JAYA MARDI MULYO GUNUNGKIDUL - Septian Oni Nurazis (JURNAL EKOBIS DEWANTARA, 2018)
Abstract The purpose of this study is to determine (1) the effect of compensation on employee performance, (2) the influence of motivation on employee performance, (3) the influence of work environment on employee performance, and (4) the influence of compensation, motivation and work environment together simultaneously on the performance of employees at the heavy equipment operator in PT Kurnia Jaya Mardi Mulyo. This research belongs to the type of quantitative research. The research population is all employees in the heavy equipment operator's part in PT Kurnia Jaya Mardi Mulyo with 145 employees, while the research sample is 50 employees. Sampling technique in this research use accidental / haphazard sampling (take a moment). Methods of data collection using questionnaire method (questionnaire), while the technique of data analysis using multiple regression analysis. The results showed (1) There was a positive effect of compensation on employee performance in heavy equipment operator in PT Kurnia Jaya Mardi Mulyo with significant value (p) = 0,010 <0,05. (2) There is a positive influence of motivation on employee performance in heavy equipment operator in PT Kurnia Jaya Mardi Mulyo with significant value (p) = 0,022 <0,05. (3) There is a positive influence of work environment on employee performance in heavy equipment operator in PT Kurnia Jaya Mardi Mulyo with significant value (p) = 0,001 <0,05. (4) There is a simultaneous (simultaneous) compensation, motivation, and work discipline effect on employee performance in heavy equipment operators section at PT Kurnia Jaya Mardi Mulyo with F calculation value of 9,051 and p value (significance) of 0.000.